Value of Local Wisdom in the Nadran Tradition at the Ki Buyut Manguntapa Site in Baregbeg District, Ciamis - Alfarizi, Rifan; Brata, Yat Rospia; Sudarto, Sudarto (JAMASAN: Jurnal Mahasiswa Pendidikan Sejarah, 2025)
Research aims to describe the existence and procession of the Nadran tradition and identify local wisdom values in Baregbeg Village, Ciamis. The Nadran tradition, as a form of gratitude for the harvest and a means of harmony between humans, ancestors, and nature, is held every Maulid at the Ki Buyut Manguntapan Site. A qualitative case study method was used, with data collected through literature, participant observation, interviews with traditional leaders, cultural experts, caretakers, and the community, as well as documentation. The analysis used an interactive model. The results show that the Nadran procession involves preparations such as traditional deliberations, fasting, collecting holy water, making seven-colored liwet rice, and cleaning graves. The main procession includes walking barefoot, praying, wearing black clothes, and scattering flowers. The local values contained therein include religiosity, mutual cooperation, cultural preservation, and ecology. This tradition serves as moral education and strengthens communal identity. The study recommends preserving this tradition as cultural heritage and integrating local values into sustainable community development.